SISTEM AKUNTANSI PEMBELIAN BARANG PADA PT XYZ - Gunawan, Enggun; Maulidah Rahma; Supadi Bambang Sutrisno (DIVERSITY: Journal of Multi Science Linearity, 2024)
This study aims to analyze and evaluate the purchasing accounting system applied at PT XYZ, as well as identify weaknesses and provide recommendations for improvement in order to improve the efficiency and accuracy of recording purchasing transactions. The research method used is a descriptive study with a qualitative approach, which includes direct observation, interviews with related parties, and document analysis. The results of the study indicate that the purchasing accounting system at PT XYZ has generally been running in accordance with standard procedures, but there are still some weaknesses, such as the lack of separation of duties in the purchasing and recording process, and delays in recording transactions. Therefore, it is recommended that PT XYZ make improvements to its internal control structure, implement an integrated computer-based accounting information system, and improve training for related employees. With these improvements, it is hoped that the purchasing process will be more effective, efficient, and accurate in recording and financial reporting